1998
DOI: 10.1128/jcm.36.8.2271-2278.1998
|View full text |Cite
|
Sign up to set email alerts
|

One-Step 2-Minute Test To Detect Typhoid-Specific Antibodies Based on Particle Separation in Tubes

Abstract: Typhoid fever is caused by Salmonella typhi. Detection of anti-S. typhi antibodies in the patient is a useful diagnostic aid. Among the various methods developed over the years for this purpose, the Widal test, based on bacterial agglutination, has remained the most widely used, even though it is neither specific nor sensitive. Its popularity stems from the fact that it is simple to use and inexpensive. We describe a new test which also uses a simple one-step procedure but is more rapid and accurate than the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 19 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…However, surprisingly, the specificity was only 25% when assessed among patients with blood culture-confirmed brucellosis, despite the use of monoclonal antibodies to Vi (an improvement to the ELISA suggested by other investigators). 20 This indicates that Brucella species may carry a Vi-like antigen, or that a Vi-like antigen is released into the urine of patients with bloodstream infections, perhaps as part of the renal component of the acute phase response. We were unable to find previous reports of Vi-like antigen from the urine of patients with brucellosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surprisingly, the specificity was only 25% when assessed among patients with blood culture-confirmed brucellosis, despite the use of monoclonal antibodies to Vi (an improvement to the ELISA suggested by other investigators). 20 This indicates that Brucella species may carry a Vi-like antigen, or that a Vi-like antigen is released into the urine of patients with bloodstream infections, perhaps as part of the renal component of the acute phase response. We were unable to find previous reports of Vi-like antigen from the urine of patients with brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Enzymelinked immunosorbent assay (ELISA) methods have been used to detect antibody to various infectious agents, 12 including Salmonella Typhi. [13][14][15][16][17][18][19][20] However, for typhoid fever, these methods have been hampered by similar limitations of sensitivity and specificity that occur with the use of the Widal agglutination test.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, such raised antibody levels frequently cannot be detected in patients with culture confirmed typhoid. Problems have also been encountered during the testing of commercial serological tests, including Typhidot and Tubex [38,39]. These assays were assessed in population-based typhoid surveillance studies in several countries and in all locations the sensitivity and specificity for Tubex and Typhidot was only around 70% and 80% respectively [40,41].…”
Section: The Limitations Of Serologymentioning
confidence: 99%
“…The a-D-Tyvelose is the immunodominant sugar of the O9 determinant. An extremely rare sugar in nature, a-D tyvelose is antigenically different from the b-D-tyvelose found in T. Spiralis or the L-tyvelose in Ascaris lumbricoides [18]. However, the O9 determinant is present not only in S. typhi but also in several other serotypes of Salmonella (serogroup D) such as S. enteritidis and S. sendai.…”
Section: Discussionmentioning
confidence: 95%
“…However, many of these bacteria are not invasive and may not stimulate a systemic antibody response. The extent to which TUBEX detects infection caused by these salmonellae or the paratyphoid serotypes remains to be investigated [18]. Previously, using the ELISA equivalent of TUBEX we found that serum samples from septicemic patients infected with Salmonella organisms not belonging to serogroup D (one with S. choleraesuis, one with S. johannesburg, and one with S. senftenberg) were negative in the test, whereas that from a patient infected systemically with S. sendai (serogroup D) was weakly positive.…”
Section: Discussionmentioning
confidence: 99%